Going long, going short, issue or liquidate? Corporate debt maturity of Mexican public firms - Farfán-Pérez, Lianet (2025)
Purpose: This paper studies the determinants of the debt maturity of Mexican-listed companies by analysing the effects on the extensive (issuing or liquidating debt) and the intensive (debt maturity renegotiation) margins. Design/methodology/approach: This study, using a Tobit model for panel data and measuring maturity as a time variable, shows that size, liquidity and leverage, among other firm characteristics, as well as the market interest rate, explain debt maturity. Additionally, the study employs the McDonald and Moffitt decomposition to determine whether the explanatory variables of maturity have a more significant effect on the decision to issue or liquidate debt or on debt maturity renegotiations. Findings: The results obtained highlight that the market interest rate negatively affects debt maturity. On the other hand, variables like size, liquidity, collateral and leverage demonstrate a positive relationship with the dependent variable. In addition, the extensive margin has a higher impact on corporate debt than the intensive margin, suggesting that firms prefer to liquidate or issue new debt rather than renegotiate preexisting contracts. Research limitations/implications: The main limitation of this study is the use of an unbalanced panel. The lack of data limits the application of specific methodologies suggested by the literature as a way to test the robustness of the estimates. Originality/value: First of all, this study adds empirical evidence of debt maturity decisions by publicly traded firms in a middle-income country such as Mexico to the existing literature on maturity choice. Second, the study treats debt maturity as a time-censored, limited variable. Finally, the authors have used the McDonald and Moffitt (1980) methodology to decompose the effect of each independent variable into extensive and intensive margins.